Convergent Effect of Application of Vermicasting, Bio-fertilizers and Moisture Harvesting Technique on Growth and Volume Production of Casuarina equisetifolia and Eucalyptus tereticornis in Tamil Nadu - Kumaravelu, G.; Krishnakumar, N.; Annapoorna, U.; Ezhumalai, S. M. (Indian Forester, 2004)
A study was undertaken to find out the effect of peripheral planting in saucers (3.0m diameter and 0.3m depth) as compared to traditional planting in Casuarina equisetifolia and Eucalyptus tereticornis for conservation of moisture there by improved tree growth. The study was undertaken in State Forestry Research Institute, Kolapakkam, Chennai. In both the planting methods vermicasting and bio-fertilizers like Vesicular Arbuscular Mycorrhizae (VAM), Azospirillum and Phosphobacteria were applied, which improve soil physical properties as well as nutrient availability. Survival was 100 percent in saucer planting as compared to 78 percent in the control. Volume production was also increased to 193 and 52.60 per cent in C. equisetifolia and E. tereticornis respectively. Cost economics for each planting method were also calculated.